Profil penderita kanker prostat di RSUP Prof. Dr. R. D. Kandou Manado periode tahun 2013–2015 - Solang, Valdo R.; Monoarfa, Alwin; Tjandra, Ferdinand (Universitas Sam Ratulangi, 2016)
Abstract: Prostate cancer is a malignant disease of urogenital system which is the second most common type of cancer in men after lung cancer. Prostate cancer is also one of the most common cause of death in male population. There is no database regarding profiles of prostate cancer in Manado. This study was aimed to determine the profile of prostate cancer patients treated at Prof. Dr. R. D. Kandou Hospital Manado in the period 2013 to 2015. This was a descriptive retrospective study in October to November 2016. Samples were taken based on secondary data of the medical record. The results showed that there were 54 patients with prostate cancer, most were found in 2015 (38.9%), age group 61-70 years old (37.0%), lived in Manado (33.3%), graduated Senior High School (64.8%), retirees (50.0%), difficult urination (44.4%), PSA levels >100 ng/ml (50.0%), histopathological of adenocarcinoma (100.0%), and Gleason score ranging from 8-10 (46.7%). Based on metastasis, 14 patients had metastasis (25.9%).Keywords: prostate cancer, profile, PSA, histopatology, Gleason scoreÂ Abstrak: Kanker prostat ialah penyakit keganasan sistem urogenital yang merupakan kanker kedua terbanyak pada pria setelah kanker paru. Kanker prostat juga merupakan salah satu penyebab terbanyak kematian pada populasi pria. Belum ditemukan data tentang profil kanker prostat di Manado. Penelitian ini bertujuan untuk mengetahui profil penderita kanker prostat yang dirawat di RSUP Prof. Dr. R. D. Kandou pada periode 2013â€“2015. Jenis penelitian ialah deskriptif retrospektif yang dilakukan pada bulan Oktober sampai November 2016. Sampel diambil berdasarkan data sekunder dari catatan rekam medik. Hasil penelitian mendapatkan 54 penderita kanker prostat, paling banyak ditemukan pada tahun 2015 (38,9%), kelompok usia 61-70 tahun (37,0%), berdiam di Kota Manado (33,3%), tamat SMA (64,8%), pensiunan (50,0%), keluhan utama sulit buang air kecil (44,4%), kadar PSA >100 ng/ml (50,0%), jenis adenokarsinoma (100,0%), dan skor Gleason 8-10 (46,7%). Berdasarkan metastasis, sebanyak 14 penderita (25,9%) mengalami metastasis. Kata kunci: kanker prostat, profil, psa, histopatologi, skor gleason